Balancing risk and fairness : A legal analysis of cell captives in South African insurance law and the obligation to treat customers fairly - Grove, Niek (University of Pretoria, 2024)
Thesis (LLM (Mercantile Law with Insurance Law and Governance))--University of Pretoria, 2023.